ETHICAL AND LEGAL ASPECTS OF INFECTIOUS DISEASES AND VACCINATION Part 3. Ethical principals of eradication of infectious diseases - O. I. Kubar (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The current article develops the conception of previous publications on ethical, legal and social aspects of the infectious diseases. Special aspect of this article is the fact, that in its frame the results of multidisciplinary analysis of the eradication of infectious disease (poliomyelitis) are presented for the first time. Such manysided investigation of the problem of the eradication of infectious disease was based on the complex use of bioethical, epidemiological, virological and socio-normative criteria that gave the opportunity to discover the ethical features and demonstrate the great value of ethical principals for the strategy of infectious diseases eradication.